A Case of Allergic Broncopulmonary Aspergillosis Associated With Hematopoietic Stem Cell Transplantation Due to Chronic Granulomatous Disease. Issue 3 (April 2019) - Malbora, Baris; Aksoylar, Serap; Ozdemir, Hamiyet H.; Ozdemir, Sinem; Kansoy, Savas
Abstract : Allergic bronchopulmonary aspergillosis is an immunologic pulmonary disorder caused by hypersensitivity to Aspergillus fumigatus . This disorder is most commonly seen in patients with poorly controlled asthma and cystic fibrosis. It is rarely reported in chronic granulomatous disease patients; however, there are no cases reported with hematopoietic stem cell transplantation in the English literature. Herein, we report a patient with chronic granulomatous disease who had hematopoietic stem cell transplantation and subsequently developed allergic bronchopulmonary aspergillosis.